PROFIL TINGKAT KESEGARAN JASMANI SISWA TATA BOGA DAN SISWA PERHOTELAN DI SMK TIGAMA PEKANBARU - M. Alfitra Fauzi; Ni Putu Nita Wijayanti; Ali Mandan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to determine the description/profile of the physical fitness level of students in the culinary department and the hospitality department at Tigama SMK Pekanbaru. The type of research used in this research is descriptive quantitative research, the research will be conducted with a population of 36 students and based on the existing population using the Proportional Stratified random sampling technique, with this each population will be used as a sample of only 20 people. Based on the results of the research and discussion that the author has described, then for the "Medium" category with an average consideration of 16.5. In detail as many as 0 students (0%) have a physical fitness level that is very low, 2 students (10%) have a physical fitness level that is less, 11 students (55%) have a moderate physical fitness level, 7 students (35%) have a physical fitness level good, and 0 male athletes (0%) have a very good Physical Fitness Level. Most of the Physical Fitness Levels owned by the Catering and Hospitality Students of SMK Tigama Pekanbaru are in the "Medium" category, amounting to 55%. Based on the results of the research, it shows that the students of catering and hospitality at SMK Tigama Pekanbaru have a moderate level of physical fitness. Because there are no students who have a very good level of physical fitness and neither students have a level of fitness that is not good. Key Words: Profile of Physical Fitness, Students, SMK Tigama Pekanbaru